Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1002/1873-3468.13367
|View full text |Cite
|
Sign up to set email alerts
|

Identification and characterization of glycosylation sites on Litopenaeus vannamei hemocyanin

Abstract: The respiratory glycoprotein hemocyanin has been implicated in immune‐related functions. Using lectin blotting, we show that the binding of shrimp (Litopenaeus vannamei) hemocyanin to concanavalin A decreases markedly with O‐glycosidase treatment but not with PNGase F. Twelve O‐glycosylation sites, three on the large hemocyanin subunit and nine on the small hemocyanin subunit (HMCs), were identified by LC‐MS/MS. Importantly, when the glycosylation sites at Thr‐537, Ser‐539, and Thr‐542 on the C terminus of HMC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 41 publications
0
9
0
Order By: Relevance
“…Thus, similar or increased binding of enzymatically or chemically deglycosylated FLH and KLH to MGL might contribute to explain their remnant immunomodulatory effects. Indeed, recent studies using the arthropodan Litopenaeus vannamei hemocyanin, a galactose-rich protein with beneficial immunostimulant and antimicrobial effects, have confirmed that its beneficial effects are promoted by its galactose-rich O- glycosylations (57). It is important to note that in this study we assessed hemocyanin binding to MR, MGL, and TLR4; however, as these proteins are multiligand molecules they might bind to several other immune receptors, such as the glycan-recognizing DC-SIGN or TLR2.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, similar or increased binding of enzymatically or chemically deglycosylated FLH and KLH to MGL might contribute to explain their remnant immunomodulatory effects. Indeed, recent studies using the arthropodan Litopenaeus vannamei hemocyanin, a galactose-rich protein with beneficial immunostimulant and antimicrobial effects, have confirmed that its beneficial effects are promoted by its galactose-rich O- glycosylations (57). It is important to note that in this study we assessed hemocyanin binding to MR, MGL, and TLR4; however, as these proteins are multiligand molecules they might bind to several other immune receptors, such as the glycan-recognizing DC-SIGN or TLR2.…”
Section: Discussionmentioning
confidence: 99%
“…In molluscan HMCs, the oligosaccharide structures of the structural subunits RvH2 from Rapana venosa hemocyanin (RvH), bc-Helix lucorum hemocyanin (bc-HlH), and Megatura crenulata keyhole limpet (KLH) reveal a complex N-glycan pattern combining typical structural features of different higher organisms; these glycosylation plays a crucial physiological role in the structural stability, immunostimulatory, and therapeutic effect of HMC (60,61). Our previous research also found that L. vannamei HMC was deglycosylated using O-glycosidase; its agglutinative activity reduced about four-to eightfold (8,38). The results from this study indicated that binding of different pathogens with HMC fractions showed diverse optimum immunological activities, and the differences in their immunological activities may be related to their glycosylation diversity.…”
Section: Discussionmentioning
confidence: 93%
“…We previously reported that HMC had an Ig-like conserved domain and could react with goat anti-human IgG, IgM, and IgA (5,19,24). Furthermore, we also found that the diversity of human IgG constituents and glycosylation levels may have functional significance (5,36,38). Therefore, to determine whether polymorphism of HMC glycosylation is associated with its functional diversity, glycan content and glycosylation level were investigated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Hex-type of glycans (for glucose, mannose, and galactose) was reported in L. vannamei in addition to the mucin-type O-glycans [68]. Among the nine O-glycosylation sites in the small subunit of hemocyanin isolated from L. vannamei, those at positions Thr537, Ser539, and Thr542 in the C terminus are of importance for its immunological function [68]. The authors reported a four-fold reduction of bacterial agglutination and a 0.2-fold reduction in the antibacterial activity after replacement of all three positions with alanine.…”
Section: Glycosylation Of E Verrucosa Hemocyanin Subunit 5 and Possimentioning
confidence: 99%